Comparative Study of Preliminarily Dehydrated Human and Bovine Erythrocyte Sensitivity to Hypertonic Stress - Aleksandrova, D. I.; Orlova, N. V.; Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2007)
Preliminary incubation of human and bovine erythrocytes in 0.4 and 1.0 M NaCl, correspondingly, results in the formation of a resistant cell state to the following 4.0 M NaCl effect. Maximum erythrocyte shrinking at the stage of preliminary incubation in moderately hypertonic media was shown as correlating with the minimum hemolysis level under cell transfer into 4.0 M NaCl-containing medium. At 37°C the level of minimum hypertonic hemolysis and minimum hematocrit value for bovine erythrocytes is lower that the similar ones, obtained for human erythrocytes. The reduction of experimental temperature down to 0°C results in hemolysis level and human erythrocyte volume decrease compared to 37°C.